CD46 facilitates entry and dissemination of human cytomegalovirus - Stein, Kathryn R. (Nat Commun, 2019)
Human cytomegalovirus (CMV) causes a wide array of disease to diverse populations of immune-compromised individuals. Thus, a more comprehensive understanding of how CMV enters numerous host cell types is necessary to further delineate the complex nature of CMV pathogenesis and to develop targeted therapeutics. To that end, we establish a vaccination strategy utilizing membrane vesicles derived from epithelial cells to generate a library of monoclonal antibodies (mAbs) targeting cell surface proteins in their native conformation. A high-throughput inhibition assay is employed to screen these antibodies for their ability to limit infection, and mAbs targeting CD46 are identified. In addition, a significant reduction of viral proliferation in CD46-KO epithelial cells confirms a role for CD46 function in viral dissemination. Further, we demonstrate a CD46-dependent entry pathway of virus infection in trophoblasts, but not in fibroblasts, highlighting the complexity of CMV entry and identifying CD46 as an entry factor in congenital infection.